Proceedings of the 35th Annual ACM Symposium on Applied Computing 2020
DOI: 10.1145/3341105.3373947
|View full text |Cite
|
Sign up to set email alerts
|

Privacy preserving cooperative computation for personalized web search applications

Abstract: With the emergence of connected objects and the development of Artiicial Intelligence (AI) mechanisms and algorithms, personalized applications are gaining an expanding interest, providing services tailored to each single user needs and expectations. They mainly rely on the massive collection of personal data generated by a large number of applications hosted from diferent connected devices. In this paper, we present CoWSA, a privacy preserving Cooperative computation framework for personalized Web Search peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Therefore, based on the above considerations, Kaaniche et al [26] designed a privacy protection framework based on user preference and proposed a secure computation based on collaboration to interfere with the configuration file. The computation includes intermediate nodes between the client and the service provider, but this method will generate more extra computation overhead.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, based on the above considerations, Kaaniche et al [26] designed a privacy protection framework based on user preference and proposed a secure computation based on collaboration to interfere with the configuration file. The computation includes intermediate nodes between the client and the service provider, but this method will generate more extra computation overhead.…”
Section: Related Workmentioning
confidence: 99%
“…However, the same random grouping is used in MG-OSLo, and the chance of being grouped with users having similar interests remains the same. Kaaniche et al proposed a decentralized solution CoWSA that empowers end-users to have control over personal data, mitigates single-point failure, ensures the security of the queries, and provides anonymity to a user [1]. User, client, WSE, third parties (TP), and trusted authorities are the five entities of CoWSA.…”
Section: Existing Workmentioning
confidence: 99%
“…e WSE stores the users' submitted queries in a query log. e WSE regularly builds and updates a user profile from the query log to provide personalized results [1]. e WSE generates revenue by analyzing the query log coupled with a user profile to provide relevant advertisements [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Two main axes based on cryptography and data perturbation are investigated. Kaaniche et al [11] designed a privacy-preserving framework for recommender systems. They suggested that a user perturbs his profile relying on a collaborative secure computation, that incorporates intermediate nodes between end-users and service providers.…”
Section: Related Workmentioning
confidence: 99%